2015
DOI: 10.1016/j.jcmg.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Effects of Intramural Course of Coronary Arteries and its Relation to Coronary Atherosclerosis

Abstract: Myocardial bridging of coronary arteries is common on CTA, but only approximately one-third of these show systolic compression. Myocardial bridging is not associated with reduced myocardial perfusion during vasodilator stress. Atherosclerosis is located predominantly proximal to myocardial bridging but atherosclerotic burden and presence of vulnerable plaques were comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 25 publications
2
27
0
2
Order By: Relevance
“…Therefore, Uusitalo et al (8), in this issue of iJACC, Absolute stress perfusion during pharmacological vasodilation was comparable in patients with and without either shallow or deep myocardial bridges. Rest perfusion was higher in patients with myocardial bridges compared to patients without bridges, but absolute stress flow was similar and well above low-flow ischemic levels.…”
Section: The Current Reportmentioning
confidence: 85%
“…Therefore, Uusitalo et al (8), in this issue of iJACC, Absolute stress perfusion during pharmacological vasodilation was comparable in patients with and without either shallow or deep myocardial bridges. Rest perfusion was higher in patients with myocardial bridges compared to patients without bridges, but absolute stress flow was similar and well above low-flow ischemic levels.…”
Section: The Current Reportmentioning
confidence: 85%
“…Previous studies have indicated that the extent of MB compression does not necessarily correlate with inducible myocardial ischemia (23), which could partly explain the lower sensitivity value compared to specificity. Furthermore, the potential clinical value of TAG for the assessment of MB lies in the exclusion of significant compression with high specificity, since myocardial perfusion defect was not noted in MB with systolic compression < 50% (24). …”
Section: Discussionmentioning
confidence: 99%
“…Functional studies validating the effect of the myocardial bridge on the myocardial blood flow demonstrate that its restriction occurs both during the systoles as well as in diastoles, and that there is a link between reversible myocardial ischemia shown by scintigraphy or by the positron emission tomography. 11 Thevasodilator pharmacological stress may not be linked to ischemia because there is no increase in the coronary contractility and subsequent systolic compression. 11 The angiotomography (angio-CT) of the coronaries is an exam that allows viewing the cardiac anatomy, especially that of the coronary arteries, in addition to analyzing the vessel walls, the presence of plaques and the diameter and course of the arteries.…”
Section: Discussionmentioning
confidence: 99%
“…11 Thevasodilator pharmacological stress may not be linked to ischemia because there is no increase in the coronary contractility and subsequent systolic compression. 11 The angiotomography (angio-CT) of the coronaries is an exam that allows viewing the cardiac anatomy, especially that of the coronary arteries, in addition to analyzing the vessel walls, the presence of plaques and the diameter and course of the arteries. Barros and collaborators demonstrated that angio-CT is highly accurate in the morphological evaluation of the myocardial bridge, allowing a noninvasive approach of its localization, length and depth, as well as of the presence of associated atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%